2012
DOI: 10.1515/bmc-2011-0053
|View full text |Cite
|
Sign up to set email alerts
|

The immortal strand hypothesis: still non-randomly segregating opinions

Abstract: Cairns first suggested a mechanism for protecting the genomes of stem cells (SCs) from replicative errors some 40 years ago when he proposed the immortal strand hypothesis, which argued for the inheritance of a so-called immortal strand by an SC following asymmetric SC divisions. To date, the existence of immortal strands remains contentious with published evidence arguing in favour of and against the retention of an immortal strand by asymmetrically dividing SCs. The conflicting evidence is derived from a div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Coined as “immortal” strand retention, it was originally proposed as a strategy to maintain DNA purity in stem cells while the copied strands, potentially carrying mutations from replication, were segregated to nonstem cell progeny ( 22 ). Whether this strategy is actually utilized by stem cells remains controversial ( 23 25 ). Immortal strand segregation has been tested in Caulobacter crescentus ( 26 , 27 ) and Bacillus subtilis ( 28 ); however, none of these studies showed any segregational strand preference between daughter cells.…”
mentioning
confidence: 99%
“…Coined as “immortal” strand retention, it was originally proposed as a strategy to maintain DNA purity in stem cells while the copied strands, potentially carrying mutations from replication, were segregated to nonstem cell progeny ( 22 ). Whether this strategy is actually utilized by stem cells remains controversial ( 23 25 ). Immortal strand segregation has been tested in Caulobacter crescentus ( 26 , 27 ) and Bacillus subtilis ( 28 ); however, none of these studies showed any segregational strand preference between daughter cells.…”
mentioning
confidence: 99%
“…'Immortal' strand retention was originally proposed as a strategy to maintain DNA purity in stem cells while the copied strands, potentially carrying mutations from replication, were segregated to non-stem cell progeny (Cairns, 1975). Whether this strategy is actually utilized by stem cells remains controversial (Lansdorp, 2007;Rando, 2007;Wakeman et al, 2012). Ancestral strand segregation has also been tested in C. crescentus (Marczynski et al, 1990;Osley and Newton, 1974) and B.…”
Section: Introductionmentioning
confidence: 99%
“…The basic assumption of the immortal strand hypothesis is that, in tissues with high cellular turnover, a subpopulation of stem cells avoids accumulating mutations arising from errors in DNA replication by systematically inheriting, for each chromosome, the chromatid with the older template strand (Cairns 1975). Accumulating evidence from studies of stem cells in various tissues has confirmed that nonrandom chromosome segregation could take place in neural (Karpowicz et al 2005) and muscle stem cells (Rocheteau et al 2012;Shinin et al 2006) (reviewed in (Wakeman et al 2012)).…”
Section: Introductionmentioning
confidence: 99%